Immunometabolic Effects of SGLT2 Inhibitors on the Th17/Treg Axis: Mechanisms, Evidence, and Implications for Therapeutic Repurposing - Hamza Alasbily; Fathi M. Sherif (Molecular Biology Reports, 2026)

Design of cholesterol-free nanophytosomes coated with natural polysaccharides for enhanced oral delivery of grape seed flavonoids - Faezeh Fathi; Reza M. Kouchaksaraee; Samad N. Ebrahimi; Anabela S.G. Costa; Alireza Fathi; Eliana B. Souto; João A.V. Prior; M. Beatriz P.P. Oliveira; Rita C. Alves (Journal of Food Engineering, 2026)

Efficient Oxidative-Extractive Desulfurization of Diesel Fuel Using Tailored Hydrophobic/Hydrophilic Imidazolium-Based Ionic Liquids and H₂O₂ Under Mild Conditions: An Attempt for Air Pollution Mitigation - Magdy T. Zaky; Fathi S. Soliman; Adel A. El-Zahhar; Majed M. Alghamdi; Amira M. Mohammed; Ahmed M. A. El Naggar; Esraa M. El-Fawal (Water, Air, & Soil Pollution, 2026)

Consistent relationships between model parameters and catchment attributes for multiple water balance models: a regionalization framework - Ahmed E. Saleh; Ayman G. Awadallah; Nabil A. Awadalla; Wael T. Aldahshoory; Mohamed M. Fathi (Hydrological Sciences Journal, 2026)

Effects of tadalafil on endothelial, angiogenic, metabolic, and microRNA biomarker profiles in sexually active men with BPH and erectile dysfunction: a randomized controlled trial - Ahmed Abomandour; Ehab A. M. El-Shoura; Basem A. Fathi; Hosny Ahmed Elewa; Ahmed M. Abd-Eldayem; Zeinab Alkasaby Zalat (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Protective effects of dietary Ocimum basilicum and Thymus vulgaris essential oils on growth performance, immune response, and disease resistance following challenge with Aeromonas hydrophila in Nile Tilapia (Oreochromis niloticus) - Salah M. Aly; Heba M. A. Abdelrazek; Nada H. Eidaroos; Samar I. Mostafa; Doaa S. Farid; Noha I. ElBanna; Mohamed Fathi (Fish Physiology and Biochemistry, 2026)

Effect of Beet Molasses Application On Wheat (Triticum aestivum L.) Germination and Seedling Growth Under Salinity Stress - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Adel A. Rezk; Metwaly Mahfouz Salem Metwaly; Hosny H. Kesba; Rania Anwar Khedr; Mohamed M. El-Mogy; Elsayed Abd Elmaksoud Abomarzokae; Wael Elmenofy; Khloud Ali Hamza (Journal of Crop Health, 2026)

Retraction Note: Nasal In-Situ Gels of Brij®-Enriched Novasomes as Optimistic Nanovesicular Carriers for Enhancing Anti-Depressant Action of Agomelatine - Tarek M. Ibrahim; Ayman M. Fathi; Nourhan A. Abdulla (AAPS PharmSciTech, 2026)

Retraction Note: Vitamin D regulates insulin and ameliorates apoptosis and oxidative stress in pancreatic tissues of rats with streptozotocin-induced diabetes - Fatima El Zahra M. Fathi; Kadry M. Sadek; Asmaa F. Khafaga; Abdel Wahab Alsenosy; Hanan A. Ghoniem; Sahar Fayez; Mohamed F. Zeweil (Environmental Science and Pollution Research, 2026)

Paclobutrazol-mediated improvement of brown spot resistance in rice seedlings under salinity stress conditions - Hossam S. El-Beltagi; Mohamed Fathi El-Nady; Adel A. Rezk; Abdelaziz M. Tahoon; Hosny Hamed Kesba; Elsayed Abd Elmaksoud Abomarzoka; Ahmed Mahmoud Ismail; Awad Mohamed El-Sayed; Wael Elmenofy; Metwaly Mahfouz Salem Metwaly (European Journal of Plant Pathology, 2026)

Integrated biocontrol of Fusarium wilt in tomato via metabolic responses and defense activation by plant growth-promoting fungi - Farqad Fathi Hasan; Mohamed S. Attia; Tarek M. Abdelghany; Amer M. Abdelaziz (Physiological and Molecular Plant Pathology, 2026)

Enhancing disease resilience in striped catfish (Pangasianodon hypophthalmus): an integrated assessment of environmental stressors, pathogen dynamics, and the protective efficacy of Spirulina platensis in Egyptian aquaculture - Ahmed Mohamed M. Hegazy; Riad H. Khalil; Mahmoud T. Amer; Hany M. R. Abdel-Latif; Mohamed Fathi (Environmental Science and Pollution Research, 2026)

Comparative parasitology and host pathophysiology: integrated assessment of ectoparasite dynamics, seasonal prevalence, and physiological impacts in co-cultured European sea bass (Dicentrarchus labrax) and gilthead sea bream (Sparus aurata) - Nashwa Abdel-Razek; Riad H. Khalil; Asmaa O. El-Ramlawy; Habiba M. Essameldin; Mohamed Fathi (Veterinary Parasitology, 2026)

Production of environmentally-friendly diesel fuel through designation of polystyrene-based hybrid nanocomposites for efficient photocatalytic desulfurization - Esraa M. El-Fawal; Ahmed M.A. El Naggar; Hussien A. El Sayed; Adel A. El-Zahhar; Majed M. Alghamdi; Fathi S. Soliman (Journal of Environmental Chemical Engineering, 2026)

Experimental and numerical investigation of flexural behavior of sustainable self-compacting geopolymer RC beams - Mohamed E. Fathi; Mohamed E. El-Zoughiby; Mohamed Mortagi; Ahmed M. Tahwia (Innovative Infrastructure Solutions, 2026)
This study presents a comprehensive experimental and numerical investigation into the flexural behavior of sustainable self-compacting geopolymer concrete ( SCGC ) beams incorporating granite waste and slag powder. While the environmental benefits of geopolymer concrete are widely studied, its structural performance, particularly when utilizing industrial wastes, remains underexplored. To address this gap, six reinforced concrete beams (100 × 150 × 1500 mm), including five SCGC beams and one Portland cement concrete ( PCC ) control beam, were tested under four-point bending. The investigation systematically evaluated the influence of key parameters: the longitudinal reinforcement ratio (0.85%, 1.34% and 2.0%) and the shear span-to-depth ratio (4.27, 4.48 and 4.7). Experimental results demonstrate that the cracking load, yield load, and ultimate flexural capacity of the SCGC beams increased with a higher reinforcement ratio and a lower shear span-to-depth ratio. Notably, the SCGC beams exhibited a higher moment capacity compared to the conventional PCC beam. A nonlinear finite element model, validated against the experimental data, provided accurate predictions of the load–deflection response and ultimate strength. The findings confirm that SCGC incorporating granite waste is a structurally viable and superior alternative to conventional concrete, with the developed model serving as a reliable tool for future design and analysis.

Immune and physiological modulation by endophytic fungi in Fusarium oxysporum f. sp. lycopersici-infected plants - Mohamed S. Attia; Tarek M. Abdelghany; Farqad Fathi Hasan; Amer M. Abdelaziz (Physiological and Molecular Plant Pathology, 2026)

Epidemiology and immunoprophylaxis of lactococcosis in European Sea bass (Dicentrarchus labrax): A comprehensive study from Egyptian Aquaculture - Talal A.M. bo Selema; Riad H. Khalil; Mahmoud M. Abotaleb; El-Sayed Hemdan Eissa; Mohamed Fathi (The Veterinary Journal, 2026)

Seasonal variations in testicular imaging, hemodynamic patterns, semen quality, hormonal, nitric oxide levels, and antioxidant profiles in male camel (Camelus dromedaries) - Elshymaa A. Abdelnaby; Ibrahim M. Ghoneim; Mohamed Marzok; Mohamed Fathi; Hossam R. El-Sherbiny; Ibrahim A. Emam (Veterinary Research Communications, 2026)

Hydrocarbon removal from refinery wastewater by photo-Fenton oxidation process: a new digital baffled photo batch reactor - M. A. Shihab; O. I. Farhan; M. I. Fathi; A. A. Hassan; A. T. Nawaf; J. I. Humadi (International Journal of Environmental Science and Technology, 2026)

Dietary Supplementation With Ulva sp. and Garlic Extracts Enhances Growth, Immune Response and Digestive Enzyme Activity in Pacific Whiteleg Shrimp ( Litopenaeus vannamei ) - Nashwa Abdel–Razek; Riad H. Khalil; Abeer A. M. Afifi; Tamer Mohammed Monir Abdelrahiem; Sameh A. Metwaly; Mohamed Fathi (Journal of Fish Diseases, 2026)
The present study investigated the effect of dietary supplementation with ethanolic extracts of Ulva sp. and garlic ( Allium sativum ) on the growth performance, muscle composition, digestive enzyme activity and immune response of Pacific whiteleg shrimp ( Litopenaeus vannamei ). A60‐day feeding trial was conducted using seven experimental diets, including a control and diets supplemented with varying concentrations of Ulva sp. extract (0.5, 1.0 and 2.0 g/kg) and garlic extract (2.0, 4.0 and 6.0 g/kg). Phytochemical analysis confirmed the presence of bioactive compounds such as flavonoids and phenolics in Ulva sp. and alkaloids, saponins and phenolic acids in garlic extract. Shrimp fed Ulva sp. extract showed significant improvements in crude protein content, essential amino acid composition and digestive enzyme activity, particularly protease and lipase activities, suggesting enhanced nutrient utilisation. Conversely, garlic extract supplementation resulted in increased fat content, indicating increased fat deposition, alongside a marked upregulation ofimmune‐related genes, including Penaeidin3 , Penaeidin4 , HSP70 and proPO , highlighting its immunostimulatory potential. The combined findings suggest that Ulva sp. extract optimally enhances protein deposition and digestive efficiency, whereas garlic extract strengthens immune responses, making both promising functional feed additives for sustainable shrimp aquaculture. Future research should explore their synergistic effects and long‐term benefits in commercial farming applications.

Comprehensive insights and In silico analysis into the emerging role of LincRNAs in lung diseases pathogenesis; a step toward ncRNA precision - Nadia M. Hamdy; Mohamed Bakr Zaki; Nourhan M. Abdelmaksoud; Shereen Saeid Elshaer; Mai A. Abd-Elmawla; Nehal I. Rizk; Doaa Fathi; Ahmed S. Doghish; Ahmed I. Abulsoud (Functional & Integrative Genomics, 2025)
Long non-coding RNAs (lncRNAs) have emerged as essential regulators of gene expression, significantly influencing various biological processes. Approximately half of all lncRNAs are classified as long intergenic non-coding RNAs (lincRNAs), which are situated among coding genes. Recent studies have documented the role of lincRNAs in the pathogenesis of lung diseases, including lung cancer, pulmonary fibrosis, and pulmonary arterial hypertension. These lincRNAs can modulate gene expression through various mechanisms, including epigenetic modifications, transcriptional regulation, and post-transcriptional regulation. By functioning as competing endogenous RNAs (ceRNAs), lincRNAs can affect the activity of microRNAs (miRNAs) and their corresponding target genes. This review delves into the intricate mechanisms by which lincRNAs contribute to the development and progression of various lung diseases. Furthermore, it discusses the potential of lincRNAs as therapeutic targets.

Regionalizing hydrologic information for runoff predictions beyond continental boundaries using machine learning - Mohamed M. Fathi; Ayman G. Awadallah (Advances in Water Resources, 2025)

A novel green μSPE platform based on magnetic Fe₃O₄-activated carbon and deep eutectic solvents for ultrasensitive determination of rhodamine B in aqueous and food matrices - Mona Moheb; Ahmad M. El-Wakil; Fathi S. Awad (Food Chemistry, 2025)

Tucumã (Astrocaryum vulgare Mart.) oil-composed nanostructured lipid carriers for topical administration: Optimization by 22 experimental factorial design and stability assessment - Maria Eugênia B. Rocha; Raquel da Ana; Faezeh Fathi; M. Beatriz P.P. Oliveira; Leticia Kakuda; Wanderley P. Oliveira; Eliana B. Souto (Chemistry and Physics of Lipids, 2025)

Escherichia coli O157:H7 prevalence in Upper Egypt: impacts on food safety and human Health, with a protection trial using natural antibacterial Piper cubeba - Nady Khairy Elbarbary; Nasreddin R. Rhouma; Mostafa M. Abdelhafeez; Ahmed Maher; Hoda S. Sherkawy; Heba M. Nageeb; Ghada Hadad; Sohaila Fathi El-Hawary; Walaa S. Hassan; Wageh S. Darwish; Eman K. Abo Shaala (World Journal of Microbiology and Biotechnology, 2025)
Escherichia coli O157:H7 has been linked to intestinal infections in humans and is thought to be a major cause of foodborne illnesses. The research is providing an update on the prevalence and toxin profile of multidrug-resistant E. coli O157:H7 in Upper Egypt, from November 2023 to February 2024. A total of 410 samples were obtained from food products, animals, water, and human stool for isolation, identification, and serotyping of multidrug-resistant E. coli O157:H7 by using traditional and molecular techniques. Furthermore, the antibacterial effect of Piper cubeba Linn. (PcL) extract against E. coli O157:H7 was studied in vitro. E. coli and E. coli O157:H7 were found to have a prevalence of 28% and 8%, respectively, with the highest occurrence in human stool. Depending on serology, 12 different E. coli serotypes were identified in the overall samples. The PCR showed that the most virulence genes found were Stx1 (42.4%), followed by uidA (39.4%), eaeA (36.4%), hlyA (30.3%), and Stx2 (15.2%). Furthermore, blaTEM (42.4%), tetA (36.4%), and Aada1 (27.3%) are the most common resistance genes. Most strains were resistant to ampicillin, penicillin G, and tetracycline (100% each), while florfenicol and ciprofloxacin were entirely sensitive. Furthermore, all concentrations of PcL extract (0.5%, 1%, 3%, and 5%) confirmed significant inhibitory activities against E. coli O157:H7 with MIC values of 0.43 mg/mL to 0.74 mg/mL and MBC values of 0.86 mg/mL to 1.76 mg/mL. These results could assist in preserving human health by increasing awareness of the dangers posed by this bacterium and lowering the prevalence of illnesses linked to E. coli O157:H7. This study proposes that PcL extract could be employed as a natural antimicrobial additive in food products, which creates new opportunities for its advancement and application in functional foods.

Rock physics application for shaly sand evaluation: A case study for Lower Nubian Sandstone Reservoir, Eastern Sirte Basin, Libya - Bahia M. Ben Ghawar; Fathi M. Salloum; Azealdeen Salih Al-Jawadi; Yaseen S. Shebani (Journal of Applied Geophysics, 2025)

Rational design of a novel, ultrasensitive molecularly imprinted polymer-based electrochemical sensor for boscalid detection in grape, tomato, and berry samples - Mahmoud Tarek; Ahmed Fathi Salem Molouk; Hany El-Shinawi; Shady M. El-Dafrawy; A.B. Abdallah (Food Chemistry, 2025)

Comparative study of bacterial pathogen prevalence and antibiotic sensitivity in Nile Tilapia: Traditional ponds vs. in-pond raceway systems in Egypt - Salah M. Aly; Osama A. Abd Allah; Noha I. ElBanna; Nahla S. Abdel-Naeim; Mohamed Fathi (Aquaculture, 2025)

Nano-spanlastics-loaded dissolving microneedle patches for ketotifen fumarate: advanced strategies for allergic conjunctivitis treatment and molecular insights - Sammar Fathy Elhabal; Mohamed El-Nabarawi; Mohamed Fathi Mohamed Elrefai; Mahmoud H. Teaima; Mai S. Shoela; Gehad M. Khamis; Ahmed Mohsen Faheem; Nada ahmed kholeif; Mahmoud Tarek Sanad (Drug Delivery and Translational Research, 2025)
Allergic conjunctivitis (AC) is the most common inflammatory disease affecting the eye's ocular surface, lid, conjunctiva, and cornea. However, effective ocular drug delivery remains challenging due to physiological barriers such as the corneal barrier. Ketotifen (KF), a widely used antihistamine and mast cell stabilizer, for treating AC and atopic asthma but belongs to the Biopharmaceutical Classification System (BCS II) have poor solubility. This study developed a multiple strategies approach for the first time, utilizing the spanlastics nano-vesicular carriers’ system (SP) containing KF using an ethanol injection method. The optimized KF-SP exhibited the smallest particle size, largest zeta-potential and entrapment efficiency ∼232.5 ± 1.9 nm, -28 ± 0.51 and 73 ± 0.02%, respectively were further incorporated into PVA/PVP polymeric dissolving microneedles (MNs) by using a micromolding technique. Scanning electron microscopy (SEM) analysis confirmed well-defined tips and morphology, and in vitro studies showed a controlled 93% cumulative release over 72 h, with a zero-order kinetic release profile, providing stable therapeutic levels. Pharmacodynamic evaluation using the Ovalbumin/Aluminium hydroxide-induced AC model demonstrated significant reductions in IgE, TNF-α, and IL-6 levels by 68.7%, 71.3%, and 67.6%, respectively, while TGF-β and IL-10 levels increased by 70.1% and 62.7% using ELISA (Enzyme-Linked Immunosorbent Assay). Gene expression analysis (IGF-1, Annexin A1, and Bcl2) further supported the therapeutic potential of this system. In this study, we proved the topical application of the multiple strategies approach KF-SP loaded PVA/PVP MNs patch offers a targeted, sustained release treatment for AC, with promising implications for prolonged ocular therapy. Graphical Abstract

Discharge variability, recharge conditions, and water supply challenges of Al Dabusiah Karstic Spring, Al Jabal Al Akhdar, Eastern Libya - H. El-Shawaihdi Moftah; M. Ibrahim Nafisa; M. Awami Younis; H. Al Riaydh Mohamed; M. Salloum Fathi (Carbonates and Evaporites, 2025)

Intensifying the charge transfer on N–(CxNx+1) catalysts system: A cutting–edge approach for sunlight driven hydrogen production† - Ejaz Hussain; Muhammad Jalil; Javeria Mansab; Muhammad Zeeshan Abid; Shahid Iqbal; Abeer Hashem; Amal M. Al-Mohaimeed; Elsayed Fathi Abd_Allah; Khezina Rafiq (Fuel, 2025)

Comparative evaluation of antioxidant status, stress, and hepatorenal biomarkers in Nile tilapia (Oreochromis niloticus) cultured in In-Pond raceway and traditional aquaculture systems - Salah M. Aly; Osama A. Abd Allah; Noha I. ElBanna; Nahla S. Abdel-Naeim; Noha S. Abdelnaeim; Mohamed Fathi (Fish Physiology and Biochemistry, 2025)
The in-pond raceway system (IPRS), is an intensive aquaculture technology that has gained attention in recent years. This study evaluated the comparative effects of In-Pond Raceway Systems (IPRS) and traditional aquaculture systems on oxidative status, stress indices, and biomarkers of liver and kidney function, as well as proteinogram in Nile tilapia (Oreochromis niloticus) over 2, 4, and 6 months. The results revealed that serum total antioxidative capacity (TAC) level were significantly lower in the IPRS group compared to the traditional system at all time points ( p < 0.01 at 2 months, p < 0.001 at 4 and 6 months), indicating oxidative stress in the IPRS. Stress markers such as cortisol and glucose levels were significantly elevated in the IPRS group at 4 and 6 months ( p < 0.05 and p < 0.001, respectively), while triglycerides and cholesterol levels were consistently higher in the IPRS group across all time points ( p < 0.001 for triglycerides, p < 0.001 at 2 months and p < 0.01 at 4 and 6 months for cholesterol). Liver function biomarkers, including alanine aminotransferase (ALT) and aspartate aminotransferase (AST), showed no significant differences between the two systems, except for a transient increase in ALT at 4 months in the IPRS group ( p < 0.05). These findings underscore the need for optimized IPRS management strategies, particularly adjusted stocking densities, to mitigate physiological stress and ensure sustainable aquaculture. The traditional system demonstrated lower stress impacts, promoting better health and metabolic stability, offering valuable insights for balanced aquaculture practices.

RETRACTED ARTICLE: Nasal In-Situ Gels of Brij®-Enriched Novasomes as Optimistic Nanovesicular Carriers for Enhancing Anti-Depressant Action of Agomelatine - Tarek M. Ibrahim; Ayman M. Fathi; Nourhan A. Abdulla (AAPS PharmSciTech, 2025)

A comprehensive assessment of smokeless tobacco (Shammah) extract: unraveling the effects on hematological parameters, antioxidant defense mechanisms, and organ health in rats - Mabrouk A. Abo-Zaid; Mohammed Abdulaziz Alfattah; Nabila Fathi Elashmawy; Hanan Ahmed Hamdi; Bedor Ali Yatimi; Latifah Abdu Hakami; Amira Ahmed Malhan; Tawfiq AlFaifi; Abadi M. Mashlawi; Sultan Areshi; Ali Hassan Amin; Khalid M. Elazab; et al. (Journal of Molecular Histology, 2025)

Study of salinity, sediment concentration, and flow intensity on floc population density in estuaries using image processing - S. Fathi Ozanbolagh; M. H. Niksokhan; A. Karbassi (International Journal of Environmental Science and Technology, 2025)

Spatiotemporal flood depth and velocity dynamics using a convolutional neural network within a sequential Deep-Learning framework - Mohamed M. Fathi; Zihan Liu; Anjali M. Fernandes; Michael T. Hren; Dennis O. Terry; C. Nataraj; Virginia Smith (Environmental Modelling & Software, 2025)

Microbial-priming of seeds with plant growth-promoting rhizobacteria and arbuscular mycorrhizal fungi for improving cotton (Gossypium barbadense L.) growth, yield and water productivity under drought stress - Hossam S. El-Beltagi; Essam Abdelaziz El-Waraky; Mohamed M. El-Mogy; Mohamed Fathi El-Nady; Ahmed Mahmoud Ismail; Elsayed B. Belal; Mohammed I. Al-Daej; Nagwa Mohamed El-Khateeb; Lamy Hamed; Metwaly Mahfouz Salem Metwaly (Biologia, 2025)

Eco-friendly synthesis and high-efficiency adsorption of potassium permanganate using a magnetic hydrochar composite derived from Calotropis procera - Tarek M. Sabry; Sabry Abd El-Hamied El-Korashy; Hossam Eldin Samer Jahin; Gasser Mohamed Khairy; Nadia Fathi Abdel Aal (Journal of Environmental Chemical Engineering, 2024)

Improvement in oocyte viability, IVM and IVF rates using of a novel FE3O4/Xylomann nanocomposite - M. Jangkhah; P. Shayegh; M.R. Ghalamboran; R. Fathi (Cryobiology, 2024)

Practicality and Economic Assessment on Using the Solar Organic Rankine Cycle as a Power Source for a Specific Membrane-based Desalination System - Mohamed Elwardany; A. S. Abdelrazik; Heba Fathi; Asmaa M. A. Omar; Nadine Abdelkawy (Water Conservation Science and Engineering, 2024)

Advancing aquaculture biosecurity: a scientometric analysis and future outlook for disease prevention and environmental sustainability - Salah M. Aly; M. Fathi (Aquaculture International, 2024)
Biosecurity plans are crucial for preventing economic and environmental impacts caused by disease outbreaks in aquaculture. These plans focus on prevention, early detection, and effective control measures. With the global threat of emerging infectious diseases and the need for sustainable production practices, the importance of biosecurity continues to grow. Scientometric analysis is a valuable tool for assessing the impact and influence of scientific research within a particular field or discipline. Scientometric analysis of aquaculture biosecurity publications reveals significant activity in the field, with the highest number of publications recorded in 2021. Cottier-Cook EJ emerged as the most prolific author, while USA and the Centre for Environment Fisheries Aquaculture Science were identified as leading contributors. Physical biosecurity measures prevent the entry of pathogens and wild fish into aquaculture systems. Biological biosecurity measures enhance immunity and reduce disease risks. Operational biosecurity measures, such as feed management and hygiene protocols, maintain animal health. Innovative technologies such as sensors and artificial intelligence improve biosecurity efficiency. Effective management of disease outbreaks requires coordination, risk assessment, and established response plans. Aquaculture biosecurity offers benefits such as disease prevention, environmental protection, and food safety, but may have disadvantages including costs and negative environmental impacts. The industry should focus on implementing effective and sustainable biosecurity measures, improving disease prevention, reducing environmental impact, and ensuring product safety and quality.

Natural antibiotics against antimicrobial resistance: sources and bioinspired delivery systems - Beatriz N. Guedes; Karolline Krambeck; Alessandra Durazzo; Massimo Lucarini; Antonello Santini; M. Beatriz P. P. Oliveira; Faezeh Fathi; Eliana B. Souto (Brazilian Journal of Microbiology, 2024)
The current burden associated to multidrug resistance, and the emerging superbugs, result in a decreased and even loss of antibiotic efficacy, which poses significant challenges in the treatment of infectious diseases. This situation has created a high demand for the discovery of novel antibiotics that are both effective and safe. However, while antibiotics play a crucial role in preventing and treating diseases, they are also associated with adverse effects. The emergence of multidrug-resistant and the extensive appearance of drug-resistant microorganisms, has become one of the major hurdles in healthcare. Addressing this problem will require the development of at least 20 new antibiotics by 2060. However, the process of designing new antibiotics is time-consuming. To overcome the spread of drug-resistant microbes and infections, constant evaluation of innovative methods and new molecules is essential. Research is actively exploring alternative strategies, such as combination therapies, new drug delivery systems, and the repurposing of existing drugs. In addition, advancements in genomic and proteomic technologies are aiding in the identification of potential new drug targets and the discovery of new antibiotic compounds. In this review, we explore new sources of natural antibiotics from plants, algae other sources, and propose innovative bioinspired delivery systems for their use as an approach to promoting responsible antibiotic use and mitigate the spread of drug-resistant microbes and infections.

Assessment of groundwater quality in arid regions utilizing principal component analysis, GIS, and machine learning techniques - Mustafa El-Rawy; Mohamed Wahba; Heba Fathi; Fahad Alshehri; Fathy Abdalla; Raafat M. El Attar (Marine Pollution Bulletin, 2024)

Therapeutic potential of grape pomace extracts: A review of scientific evidence - Tatiane O.X. Machado; Isabella Portugal; Helena de A.C. Kodel; Daniela Droppa-Almeida; Marcos Dos Santos Lima; Faezeh Fathi; M. Beatriz P.P. Oliveira; Ricardo L.C. de Albuquerque-Júnior; Cláudio Dariva; Eliana B. Souto (Food Bioscience, 2024)

Cumulative assessment of Diplectanum spp. occurrence, prevalence, and pathological impact in Dicentrarchus labrax from varied Egyptian fish farms - Salah Aly; El-Sayed Abou El-gheit; Hussien Osman; Mona M. Tolba; Habiba M. Essameldin; Mohamed Fathi (Veterinary Parasitology, 2024)

Enhanced Biocompatibility by Evaluating the Cytotoxic and Genotoxic Effects of Magnetic Iron Oxide Nanoparticles and Chitosan on Hepatocellular Carcinoma Cells (HCC) - Heba M. Fahmy; Samar Shekewy; Fathi A. Elhusseiny; Ahmed Elmekawy (Cell Biochemistry and Biophysics, 2024)
Hepatocellular carcinoma (HCC), the fifth most prevalent cancer worldwide, is influenced by a myriad of clinic-pathological factors, including viral infections and genetic abnormalities. This study delineates the synthesis, characterization, and the biological efficacy of iron oxide nanoparticles (Fe 3 O 4 ) and chitosan-coated iron oxide nanoparticles (Fe 3 O 4 -CS) against HCC. Analytical methods confirmed the successful synthesis of both nanoparticles, with Fe 3 O 4 -CS demonstrating a smaller, uniform spherical morphology and distinct surface and magnetic properties attributable to its chitosan coating. The prepared materials were analyzed using various techniques, and their potential cytotoxic effects on HepG2 cancer cells line for HCC were investigated. In biological evaluations against HepG2 cells, a notable distinction in cytotoxicity was observed. Fe 3 O 4 showed modest anticancer activity with an IC50 of 383.71 ± 23.9 µg/mL, whereas Fe 3 O 4 exhibited a significantly enhanced cytotoxic effect, with a much lower IC50 of 39.15 ± 39.2 µg/mL. The Comet assay further evidenced Fe 3 O 4 -CS potent DNA damaging effect, showcasing its superior ability to induce apoptosis through extensive DNA fragmentation. Biochemical analyses integrated into our results reveal that Fe 3 O 4 -CS not only induces significant DNA damage but also markedly alters oxidative stress markers. Compared to control and Fe 3 O 4 -treated cells, Fe 3 O 4 -CS exposure significantly elevated levels of oxidative stress markers: superoxide dismutase (SOD) increased to 192.07 U/ml, catalase (CAT) decreased to 0.03 U/L, glutathione peroxidase (GPx) rose dramatically to 18.76 U/gT, and malondialdehyde (MDA) levels heightened to 30.33 nmol/gT. These results underscore the potential of Fe 3 O 4 -CS nanoparticles not only in inducing significant DNA damage conducive to cancer cell apoptosis but also in altering enzymatic activities and oxidative stress markers, suggesting a dual mechanism of action that may underpin their therapeutic advantage in cancer treatment. Our findings advocate for the further exploration of Fe 3 O 4 -CS nanoparticles in the development of anticancer drugs, emphasizing their capability to trigger oxidative stress and enhance antioxidant defense mechanisms.

Evaluation of the Therapeutic Effect of Curcumin-Conjugated Zinc Oxide Nanoparticles on Reserpine-Induced Depression in Wistar Rats - Heba M. Fahmy; Fatmaalzahraa A. Aboalasaad; Ayman S. Mohamed; Fathi A. Elhusseiny; Yasser A. Khadrawy; Ahmed Elmekawy (Biological Trace Element Research, 2024)
Depression, a devastating brain illness, necessitates the exploration of novel antidepressant treatments. We evaluated the antidepressant effects of free curcumin, zinc oxide nanoparticles (ZnO NPs), and curcumin-conjugated zinc oxide nanoparticles (Zn(cur)O NPs). The nanoformulations were extensively characterized using advanced techniques. An acute toxicity study ensured the safety of Zn(cur)O NPs. Rats were assigned to one of five groups: control, reserpine-induced depression model, treatment with ZnO NPs, free curcumin, or Zn(cur)O NPs. Behavioral assessments (forced swimming test [FST] and open-field test [OFT]) and neurochemical analyses were conducted. Zn(cur)O NPs exhibited superior efficacy in ameliorating reserpine-induced behavioral and neurochemical effects compared to free curcumin and ZnO NPs. The reserpine-induced model displayed reduced motor activity, swimming time, and increased immobility time in the FST and OFT. Treatment with Zn(cur)O NPs 45 mg/kg significantly improved motor activity and reduced immobility time. Furthermore, Zn(cur)O NPs decreased malondialdehyde (MDA) levels while increasing reduced glutathione (GSH) and catalase (CAT) levels. Additionally, concentrations of serotonin (5-HT) and norepinephrine (NE) increased. In conclusion, curcumin-conjugated zinc oxide nanoparticles demonstrate potent antidepressant effects, alleviating depressive-like behavior in rats. These findings support Zn(cur)O NPs as a promising therapeutic strategy for depression management, warranting further investigation and clinical validation.

Effects of natural and synthetic immunostimulants on growth, feed utilization, immune status, and disease resistance against vibriosis in sea bream (Sparus aurata) - Salah M. Aly; Noha I. ElBanna; Mohamed A. Elatta; Mai Hegazy; Mohamed Fathi (Aquaculture International, 2024)
The objective of this study was to explore the effects of black seed ( Nigella sativa ) and AQUA-IMMUNOPROTECT® on growth, feed utilization, serum constituents, and disease resistance against vibriosis in gilthead sea bream juveniles. The research involved three groups: T C (control) received a basal diet, T SI (received a basal diet with 2% AQUA-IMMUNOPROTECT®), and T NS (received a basal diet with 2% N. sativa ). The experiment period extended for 2 months. Results revealed a significant rise in erythrogram (RBCs, HB, and PCV %), leucogram (total differential leucocytic count), serum total protein, and globulin in gilthead sea bream treated with 2% Nigella sativa supplemented diets after an 8-week trial. No substantial variations were found in liver enzymes, urea, uric acid, and creatinine between the groups. Respiratory burst activity was notably greater in the N. sativa group after 2 months of feeding compared to the other groups. In the experimental challenge, the control group experienced higher mortality rates than the other groups following an IP injection of V. harveyi at a dose of 10 6 CFU per 0.5 ml/fish (10 6 fish/challenge). Overall, the findings of this research indicate that N. sativa can enhance non-specific immunity and minimize susceptibility and pathogenicity to V. harveyi in gilthead sea bream.

Pandemic impacts on the water quality: statistical analysis and spatiotemporal monitoring via GIS maps - B. El Fathi; N. Idrissi; F. El Madani; F. El Hassani; Z. Rais; M. Lghamour; M. Idrissi; N. Mazigh; A. Ouallali; A. Taleb (Sustainable Water Resources Management, 2024)

Studies on Vibrio campbellii as a newly emerging pathogen affecting cultured seabream (Sparus aurata) in Egypt - Salah M. Aly; Mohamed A. Elatta; Noha I. ElBanna; Mustafa A. El-Shiekh; Mahmoud S. Kelany; Mohamed Fathi; Mahmoud Mabrok (Aquaculture International, 2024)
Aquaculture has become a crucial solution for addressing food scarcity worldwide, including Egypt. However, the intensification of aquaculture practices has led to water quality degradation and the emergence of new fish diseases, such as vibriosis . This study aimed to investigate the molecular typing, prevalence, pathogenicity, and environmental risk factors associated with Vibrio campbellii ( V. campbellii ) in cultured seabream. A total of 160 gilthead seabream, Sparus aurata (40 fish/season), along with 48 water samples ( n = 12/season) were collected randomly and seasonally from private fish farms in the Suez Canal area over the course of a year for laboratory examinations. Clinical and postmortem inspections revealed characteristic signs and lesions similar to those observed in well-known vibrios infections. Bacteriological tests revealed the presence of V. campbellii strains in various internal organs. The isolated bacteria were identified morphologically, biochemically, and molecularly by targeting the 16S rRNA conserved gene. Histopathological examination was performed, providing insights into pathogen-induced tissue damage and septicemic disease progression. The prevalence of V. campbellii showed variable patterns across seasons, with higher proportions of cases in the summer. To examine the diagnostic performance of several water quality measures, the Receiver Operating Characteristic (ROC) curve analysis was performed. The results showed various levels of predictive performance for the outcome variable V. campbellii , with ammonia serving as a significant predictor for the variable of interest. The challenge results indicated a 100% survival rate in the controls, whereas the challenged group exhibited a mortality number of 6.00 ± 0.58, resulting in a survival rate of 70.00 ± 2.89%. The current study emphasizes how crucial it is to take into account seasonal parameters to comprehend the prevalence and seriousness of vibriosis in mariculture. The findings add to a better understanding of the impact of water quality on fish disease emergence and can benefit the creation of appropriate management measures to ensure aquaculture populations’ health and well-being.

Chlorella in aquaculture: challenges, opportunities, and disease prevention for sustainable development - Salah M. Aly; Noha I. ElBanna; M Fathi (Aquaculture International, 2024)
Aquaculture is the farming of aquatic organisms like fish, crustaceans, mollusks, and aquatic plants, which has become a crucial source of protein and income. However, bacterial infections pose a significant challenge to the aquaculture industry and traditional treatments, such as antibiotics and chemicals, have limitations and environmental concerns. Disease prevention and control measures, such as the use of probiotics, vaccines, and biosecurity measures, are essential for the sustainable development of the aquaculture industry. Further research is also needed to develop more effective and sustainable strategies for the prevention and control of bacterial fish pathogens in aquaculture, where alternative treatments such as herbal extracts, essential oils, and probiotics require further investigation for efficacy and safety. Microalgae, particularly Chlorella, have potential applications in various industries such as biofuels, pharmaceuticals, and wastewater treatment. However, their large-scale production and commercialization face challenges. Safety of Chlorella to fish is a crucial issue that requires careful evaluation, with hematology being an essential tool to assess its effects on fish health and physiology. Studies show that Chlorella is safe for fish and does not have adverse effects on growth, survival, or immune system function. Chlorella is a safe and sustainable option for aquaculture, free from harmful chemicals and antibiotics. The Green Water System utilizes Chlorella as a natural filter and nutrient recycler, improving water quality and providing a well-balanced diet for aquatic animals. This eco-friendly approach also enhances fish immune systems, growth rates, and survival rates. The scientometric review shows significant research activity, with Chang JS being a prominent author and People’s R China and the Chinese Academy of Sciences leading in contributions. The use of Chlorella shows promise as an alternative treatment for bacterial fish pathogens in aquaculture due to its antibacterial properties, safety, and sustainability. However, challenges such as cost-effectiveness and standardization need to be addressed for successful implementation in the aquaculture industry.

Biotechnological approaches for the production of hypericin and other important metabolites from the genus Hypericum - Jameel M. Al-Khayri; Sudheer Wudali Narasimha; Amaranatha Reddy Vennapusa; Praveen Nagella; Wael Fathi Shehata; Muneera Q. Al-Mssallem (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Therapeutic Peptides and Proteins: Stabilization Challenges and Biomedical Applications by Means of Nanodelivery Systems - Elisa Berselli; Carlotta Coccolini; Giovanni Tosi; Evren H. Gökçe; M. Beatriz P. P. Oliveira; Faezeh Fathi; Karolline Krambeck; Eliana B. Souto (International Journal of Peptide Research and Therapeutics, 2024)
The delivery of peptides and proteins usually faces formulation development challenges attributed to the difficulties encountered in their stabilization. Nanoparticles offer an alternative to improve the physicochemical stability of such biomacromolecules, while increasing their bioavailability by overcoming biological absorption barriers. With this review, we aim to discuss the stability problems of proteins and peptides that have driven the scientific community to find in nanotechnology a valid alternative for oral administration of biomolecules. In addition, we describe the most commonly used nanoparticles for this purpose (e.g., polymers such as polylactic acid, poly(lactic-co-glycolic acid), polycaprolactone, modified chitosan, and lipids such as oil-in-water nanoemulsions, self-emulsified drug delivery systems, solid lipid nanoparticles, nanostructured lipid carriers, liposomes, as well as hybrid systems like micelles), and we show some of the most important recent applications of these nanoparticles for the delivery of proteins and peptides, including for the treatment of diabetes, viruses (such as HIV), cancer, as well as in the development of vaccines.

Automated diagnosis of EEG abnormalities with different classification techniques - Essam Abdellatef; Heba M. Emara; Mohamed R. Shoaib; Fatma E. Ibrahim; Mohamed Elwekeil; Walid El-Shafai; Taha E. Taha; Adel S. El-Fishawy; El-Sayed M. El-Rabaie; Ibrahim M. Eldokany; Fathi E. Abd El-Samie (Medical & Biological Engineering & Computing, 2023)

Comprehensive analysis of Vibrio alginolyticus : Environmental risk factors in the cultured Gilthead seabream ( Sparus aurata ) under seasonal fluctuations and water parameter alterations - Salah M. Aly; Mohamed A. Elatta; Noha I. ElBanna; Mustafa A. El‐Shiekh; Mahmoud Mabrok; Mahmoud S. Kelany; Mohamed Fathi (Journal of Fish Diseases, 2023)
This study aimed to investigate the relationship between seasonal variations, water parameters and the prevalence of Vibriosis in Gilthead seabream. A total of 160 Gilthead seabream fish were sampled over the course of 1 year from private earthen pond farms in the Suez Canal area and examined for abnormalities and internal lesions. Vibrio alginolyticus , the causative agent of Vibriosis, was isolated and characterized from the sampled Gilthead seabream fish. The study revealed a significant correlation between different seasons and the prevalence of V. alginolyticus , with lower occurrence during autumn. Analysis of water parameters showed that toxic ammonia concentration was not effective in distinguishing between positive and negative cases of V. alginolyticus . Dissolved oxygen showed weak predictive ability for the occurrence of V. alginolyticus , while temperature demonstrated moderate potential as a predictor of its prevalence. pH values, organic matter concentrations and salinity showed no significant association with the occurrence of V. alginolyticus . Experimental challenges highlighted the vulnerability of Gilthead seabream to V. alginolyticus and emphasized the impact of environmental factors, such as pH and toxic ammonia, on their mortality and survival. The study emphasizes the importance of considering seasonal changes and water quality parameters in managing V. alginolyticus in mariculture. It underscores the need for careful monitoring and control of environmental factors to ensure the health and well‐being of cultured fish populations. The findings contribute to our understanding of Vibriosis management and provide valuable insights for developing effective strategies in the aquaculture industry.

Thymus satureioides Coss. combats oral ulcer via inhibition of inflammation, proteolysis, and apoptosis - Mahmoud H. Elbatreek; Ayman M. Fathi; Ismail Mahdi; Mohamed A. O. Abdelfattah; Mona F. Mahmoud; Mansour Sobeh (Inflammopharmacology, 2023)

Biosynthesized silver nanoparticles (Ag NPs) from isolated actinomycetes strains and their impact on the black cutworm, Agrotis ipsilon - Inas M. Abou El-Enain; Enayat M. Elqady; Eman El-said; Hend H.A. Salem; Naglaa Fathi Badr; Ghada E. Abd-Allah; Mohamed M. Rezk (Pesticide Biochemistry and Physiology, 2023)

Biomedical and Nutritional Applications of Lactoferrin - Carlotta Coccolini; Elisa Berselli; Cristina Blanco-Llamero; Faezeh Fathi; M. Beatriz P. P. Oliveira; Karolline Krambeck; Eliana B. Souto (International Journal of Peptide Research and Therapeutics, 2023)
Lactoferrin (Lf) is a glycoprotein belonging to the transferrin family, which can be found in mammalian milk. It was first isolated from bovine milk in the 1930s, and later in the 1960s, it was determined from human milk. This multifunctional protein has the specific ability to bind iron. It plays various biological roles, such as antibacterial, antiviral, antifungal, anti-tumour, anti-obesity, antioxidant, anti-inflammatory and immunomodulatory activities. There are several studies describing its use against in various cancer cell lines (e.g., liver, lung and breast) and the glycoprotein has even been reported to inhibit the development of experimental metastases in mice. Previous studies also suggest Lf-mediated neuroprotection against age-related neurodegenerative diseases and it is also expected to attenuate aging. More recently, Lf has been proposed as a potential approach in COVID-19 prophylaxis. In this review, we discuss the recent developments about the biological activities of this pleiotropic glycoprotein that will reason the exploitation of its biomedical and supplementary nutritional value.

Expression profile of genes related to pregnancy maintenance in Dromedary Camel during the first trimester - Ola Adel; Sally Ibrahim; Karima Mahmoud; Samaa M. Galal; Mohamed Fathi; Adel A.M. Seida (Animal Reproduction Science, 2023)

An Improved Monthly Water Balance GR2M Model with a Seasonally Variable Parameter - Mohamed M. Fathi; Ayman G. Awadallah; Wael Aldahshoory (Journal of Hydrology, 2023)

Evaluating strategies for sustainable recovery and recycling of plastic waste in the West Bank of Palestine: The perspectives of plastic companies - Dalia Saadeh; Issam A. Al-Khatib; Fathi M. Anayah (Environmental Monitoring and Assessment, 2023)

Correction to: Vitamin D regulates insulin and ameliorates apoptosis and oxidative stress in pancreatic tissues of rats with streptozotocin‑induced diabetes - Fatima El Zahra M. Fathi; Kadry M. Sadek; Asmaa F. Khafaga; Abd Elwahab A. Alsenosy; Hanan A. Ghoneim; Sahar F. Mahmoud; Mohamed M. Zeweil (Environmental Science and Pollution Research, 2022)

RETRACTED ARTICLE: Vitamin D regulates insulin and ameliorates apoptosis and oxidative stress in pancreatic tissues of rats with streptozotocin-induced diabetes - Fatima El Zahra M. Fathi; Kadry M. Sadek; Asmaa F. Khafaga; Abdel Wahab Alsenosy; Hanan A. Ghoniem; Sahar Fayez; Mohamed F. Zeweil (Environmental Science and Pollution Research, 2022)
This study was designed to evaluate the potential therapeutic efficacy of vitamin D (Vit D) in averting the harmful effects of type 2 diabetes mellitus (T2D). Forty male Wistar rats were allotted into four groups: (1) the control, (2) Vit D, (3) streptozotocin (STZ), and (4) STZ + Vit D groups. Rats co-treated with Vit D had significantly ( p < 0.05) decreased levels of cortisol; proinflammatory cytokines, including interleukin-6 (IL-6); and malondialdehyde (MDA). Meanwhile, the levels of insulin significantly ( p < 0.05) increased, whereas the activity of the antioxidant system, including glutathione (GSH), superoxide dismutase (SOD), catalase, and total antioxidant capacity (TAC), significantly ( p < 0.05) decreased. Histopathological examination revealed the destruction of beta cells in the islets of Langerhans in rats with diabetes. Meanwhile, immunoexpression revealed an increase in the immunoreactivity of caspase-3 and endothelial nitric oxide synthase and a reduction in the immunoreactivity of insulin in rats with diabetes. In conclusion, Vit D ameliorated the harmful biochemical impact of diabetes mellitus, probably by increasing insulin secretion and sensitivity, ameliorating β-cell function, and decreasing cortisol levels; also, the anti-inflammatory effect of Vit D reduces the number of proinflammatory cytokines (e.g., IL-6) and increases the activity of the antioxidant system, such as GSH, SOD, TAC, and catalase while reducing lipid peroxidation enzymes (e.g., MDA).

Impact of structural fabric on development of karst aquifer in Ayn Zayanah-Al Coeffiah area in Benghazi plain, NE Libya - Fathi M. Salloum; Ahmed A. Al Amin; Moftah H. El-Shawaihdi; Maher A. El Amawy; Ahmed M. Muftah; Mohammed H. Al Riaydh (Carbonates and Evaporites, 2022)

Evaluating linked treatment-reservoir operation system to mitigate nitrate concentration of agricultural runoff - M. Sedighkia; Z. Fathi; A. Abdoli (International Journal of Environmental Science and Technology, 2022)

Prevalence, population dynamics and associated natural enemies of Tomato Leafminer, Tuta absoluta, in Egypt - El-Said M. Hassan; Ibrahim I. Mesbah; Fathi A. Ali; Ibrahim A. El-Shesheny (International Journal of Tropical Insect Science, 2022)

Influence of environmental factors on biology and catch composition of Barbonymus schwanenfeldii in a tropical lake, northern Malaysia: implications for conservation planning - Mustafizur M. Rahman; Ahmad Fathi (Environmental Science and Pollution Research, 2022)

Influences of environmental parameters and phytoplankton productivity on benthic invertebrates in a tropical oligotrophic lake, northern Malaysia - Mustafizur M. Rahman; Ahmad Fathi; Stephen R. Balcombe; Bryan Nelson; Akbar John (Environmental Science and Pollution Research, 2021)

Modeling and Reducing the Effect of Geometric Uncertainties in Intracranial Aneurysms with Polynomial Chaos Expansion, Data Decomposition, and 4D-Flow MRI - Isaac Perez-Raya; Mojtaba F. Fathi; Ahmadreza Baghaie; Raphael Sacho; Roshan M. D’Souza (Cardiovascular Engineering and Technology, 2021)

Estimation of Regional Sub-Daily Rainfall Ratios Using SKATER Algorithm and Logistic Regression - Mohamed M. Fathi; Ayman G. Awadallah; Nabil A. Awadallah (Water Resources Management, 2021)

Mapping habitat suitability for gastrointestinal nematodiasis of ruminants in southern Caspian Sea littoral: a predicted risk pattern model based on the MaxEnt - M. Shadman; B. Meshgi; S. Fathi; A. A. Hanafi-Bojd; M. Majidi-Rad; G. Modabbernia (Tropical Animal Health and Production, 2020)

Assessing the soil-structure interaction effects by direct method on the out-of-plane behavior of masonry structures (case study: Arge-Tabriz) - Ahmad Fathi; Arjang Sadeghi; M. Reza Emami Azadi; Nader Hoveidae (Bulletin of Earthquake Engineering, 2020)

Trichodinids and monogeneans infestation among Nile tilapia hatcheries in Egypt: prevalence, therapeutic and prophylactic treatments - S. Aly; M. Fathi; E. M. Youssef; M. Mabrok (Aquaculture International, 2020)

Two Efficient Hybrid Methods for Enhancing Pan-Sharpening of Multi-spectral Images Transmitted from Satellite to Ground Stations - Tamer M. Talal; Gamal Attiya; Mohamed R. Metwalli; Fathi E. Abd El-Samie; M. I. Dessouky (Journal of the Indian Society of Remote Sensing, 2019)

Improving the Resolution of 3-D Resistivity Surveys Along the Perimeter of a Confined Area Using Optimized Arrays - Fathi M. Abdullah; Meng H. Loke; Mohd Nawawi; Khiruddin Abdullah (Pure and Applied Geophysics, 2019)

Impact of Clinically Relevant Elliptical Deformations on the Damage Patterns of Sagging and Stretched Leaflets in a Bioprosthetic Heart Valve - Deepa Sritharan; Parinaz Fathi; Jason D. Weaver; Stephen M. Retta; Changfu Wu; Nandini Duraiswamy (Cardiovascular Engineering and Technology, 2018)

Detection of Tilapia Lake Virus in Egyptian fish farms experiencing high mortalities in 2015 - P Nicholson; M A Fathi; A Fischer; C Mohan; E Schieck; N Mishra; A Heinimann; J Frey; B Wieland; J Jores (Journal of Fish Diseases, 2017)

Antixenosis and Antibiosis Resistance in Rice Cultivars against Chilo suppressalis (Walker) (Lepidoptera: Crambidae) - M A Tabari; S A A Fathi; G Nouri-Ganbalani; A Moumeni; J Razmjou (Neotropical Entomology, 2017)

Mechanistic investigation of hepato-protective potential for cucurbitacins - Hajer M. Arjaibi; Mahmoud S. Ahmed; Fathi T. Halaweish (Medicinal Chemistry Research, 2017)

Tissue Engineered Human Amniotic Membrane Application in Mouse Ovarian Follicular Culture - M. Motamed; Z. Sadr; M. R. Valojerdi; A. Moini; S. Oryan; M. Totonchi; B. Ebrahimi; S. Maroufizadeh; E. Taghiabadi; R. Fathi (Annals of Biomedical Engineering, 2017)

Optimizing the phosphorus use in cotton by using CSM-CROPGRO-cotton model for semi-arid climate of Vehari-Punjab, Pakistan - Asad Amin; Wajid Nasim; Muhammad Mubeen; Muhammad Nadeem; Liaqat Ali; Hafiz Mohkum Hammad; Syeda Refat Sultana; Khawar Jabran; M. Habib ur Rehman; Shakeel Ahmad; Muhammad Awais; Atta Rasool; et al. (Environmental Science and Pollution Research, 2017)

Genetic Relationship and Diversity Analysis of Faba Bean (Vicia Faba L. var. Minor) Genetic Resources Using Morphological and Microsatellite Molecular Markers - Ghassen Abid; Dominique Mingeot; Sripada M. Udupa; Yordan Muhovski; Bernard Watillon; Khaled Sassi; Mahmoud M’hamdi; Fatma Souissi; Khediri Mannai; Fathi Barhoumi; Moez Jebara (Plant Molecular Biology Reporter, 2015)

Crack Propagation and Its Shear Mechanisms in the Bovine Descending Aorta - Henry W. Haslach; Lauren N. Leahy; Parinaz Fathi; Joshua M. Barrett; Amanda E. Heyes; Thomas A. Dumsha; Eileen L. McMahon (Cardiovascular Engineering and Technology, 2015)

Hydrogeochemistry of groundwater from karstic limestone aquifer highlighting arsenic contamination: case study from Jordan - Mustafa Al Kuisi; Abdulkader M. Abed; Kholoud Mashal; Ghazi Saffarini; Fathi Saqhour (Arabian Journal of Geosciences, 2015)

An efficient fusion technique for quality enhancement of remotely sensed images - Amr M. Ragheb; Mohammed Amoon; Hanaa Abdallah; Saleh M. Elkaffas; Tarek A. El-Tobely; S. Khamis; Mohamed E. Nasr; Fathi E. Abd El-Samie (Applied Geomatics, 2014)

Efficient pan-sharpening of satellite images with the contourlet transform - Mohamed R. Metwalli; Ayman H. Nasr; Osama S. Faragallah; El-Sayed M. El-Rabaie; Alaa M. Abbas; Saleh A. Alshebeili; Fathi E. Abd El-Samie (International Journal of Remote Sensing, 2014)

A novel antioxidant phenanthrenoid dimer from Juncus acutus L. - Fathi A.A. Behery; Zain-Elabdin M. Naeem; Galal T. Maatooq; Mohamed M.A. Amer; Atallah F. Ahmed (Natural Product Research, 2013)

Parasitism and developmental parameters of the parasitoid Diadegma majale (Gravenhorst) in control of Plutella xylostella (L.) on selected cultivars of canola - Seyed Ali Asghar Fathi; Maryam Bozorg-Amirkalaee; Rana M. Sarfraz; Hoshang Rafiee-Dastjerdi (BioControl, 2012)

Potential causes of enhanced transfer of mercury to St. Lawrence River Biota: implications for sediment management strategies at Cornwall, Ontario, Canada - J. J. Ridal; L. E. Yanch; A. R. Fowlie; N. R. Razavi; T. M. Delongchamp; E. S. Choy; M. Fathi; P. V. Hodson; L. M. Campbell; J. M. Blais; M. B. C. Hickey; E. Yumvihoze; et al. (Hydrobiologia, 2010)

Drinking water treatment residuals as an amendment to alkaline soils: Effects on the growth of corn and phosphorus extractability - A. M. Mahdy; E. A. Elkhatib; N. O. Fathi (International Journal of Environmental Science and Technology, 2007)

Cone penetration resistance of calcareous sand - Fathi M. Shaqour (Bulletin of Engineering Geology and the Environment, 2007)

Reverse Iontophoresis as a Noninvasive Tool for Lithium Monitoring and Pharmacokinetic Profiling - Benoît Leboulanger; Marc Fathi; Richard H. Guy; M. Begoña Delgado-Charro (Pharmaceutical Research, 2004)

Palaeolimnological responses of nine North African lakes in the CASSARINA Project to recent environmental changes and human impact detected by plant macrofossil, pollen, and faunal analyses - Hilary H. Birks; Sylvia M. Peglar; Ian Boomer; R.J. Flower; M. Ramdani; P.G. Appleby; A.E. Bjune; S.T. Patrick; M.M. Kraïem; A.A. Fathi; H.M.A. Abdelzaher (Aquatic Ecology, 2001)

Phytoplankton communities of North African wetland lakes: the CASSARINA Project - A.A. Fathi; H.M.A. Abdelzaher; R.J. Flower; M. Ramdani; M.M. Kraïem (Aquatic Ecology, 2001)

Terrestrial pollen record of recent land-use changes around nine North African lakes in the CASSARINA Project - Sylvia M. Peglar; Hilary H. Birks; H. J. B. Birks; A.A. Fathi; R.J. Flower; M.M. Kraïem; S.T. Patrick; M. Ramdani (Aquatic Ecology, 2001)

Recent environmental change in North African wetland lakes: diatom and other stratigraphic evidence from nine sites in the CASSARINA Project - R.J. Flower; S. Dobinson; M. Ramdani; M.M. Kraïem; C. Ben Hamza; A.A. Fathi; H.M.A. Abdelzaher; H.H. Birks; P.G. Appleby; J.A. Lees; E. Shilland; S.T. Patrick (Aquatic Ecology, 2001)

Recent environmental change in North African wetland lakes: a baseline study of organochlorine contaminant residues in sediments from nine sites in the CASSARINA Project - A.J. Peters; K.C. Jones; R.J. Flower; P.G. Appleby; M. Ramdani; M.M. Kraïem; A.A. Fathi (Aquatic Ecology, 2001)

Zooplankton (Cladocera, Ostracoda), Chironomidae and other benthic faunal remains in sediment cores from nine North African wetland lakes: the CASSARINA Project - Mohammed Ramdani; Roger J. Flower; Najat Elkhiati; with contributions from Hilary H. Birks; Mohammed M. Kraïem; Adel A. Fathi (Aquatic Ecology, 2001)

North African wetland lakes: characterization of nine sites included in the CASSARINA Project - Mohammed Ramdani; Roger J. Flower; Najat Elkhiati; Mohammed M. Kraïem; Adel A. Fathi; Hilary H. Birks; Simon T. Patrick (Aquatic Ecology, 2001)

Radiometrically determined dates and sedimentation rates for recent sediments in nine North African wetland lakes (the CASSARINA Project) - P.G. Appleby; H.H. Birks; R.J. Flower; N. Rose; S.M. Peglar; M. Ramdani; M.M. Kraïem; A.A. Fathi (Aquatic Ecology, 2001)

Open water zooplankton communities in North African wetland lakes: the CASSARINA Project - Mohammed Ramdani; Najat Elkhiati; Roger J. Flower; Hilary H. Birks; Mejdidine M. Kraïem; Adel A. Fathi; Simon T. Patrick (Aquatic Ecology, 2001)

Some observations on the age and growth of thin-lipped grey mullet, Liza ramada Risso, 1826 (Pisces, Mugilidae) in three North African wetland lakes: Merja Zerga (Morocco), Garâat Ichkeul (Tunisia) and Edku Lake (Egypt) - M.M. Kraïem; C. Ben Hamza; M. Ramdani; A.A. Fathi; H.M.A. Abdelzaher; R.J. Flower (Aquatic Ecology, 2001)

The effect of community-acquired pneumonia on plasma esterases in older people - Khaled Abou-Hatab; Kandasamy Ganeshalingam; M. Sinead O'Mahony; Fathi Giurani; Sarju Patel; Kenneth Woodhouse (European Journal of Clinical Pharmacology, 2001)